Changes of DNA Methylation Pattern in Metabolic Pathways Induced by High-Carbohydrate Diet Contribute to Hyperglycemia and Fat Deposition in Grass Carp (Ctenopharyngodon idellus) - Cai, Wen-Jing; Liang, Xu-Fang; Yuan, Xiao-Chen; Li, Ai-Xuan; He, Shan (Frontiers in Endocrinology, 2020)
Although studies have determined that epigenetics plays an essential role in regulating metabolism in mammals, research on nutrition related DNA methylation remains to be lack in teleosts. In the present study, we provided hepatic whole-genome DNA methylation analysis in grass carp fed with moderate or excessive carbohydrate level diet. Although high-carbohydrate diet significantly changed mRNA expression levels of metabolic genes, it did not affect the global genomic DNA methylation levels in grass carp liver. However, compared with the control group, 3972 genes were hyper-methylated and 2904 genes were hypo-methylated in the promoter region. Meanwhile, 10711 genes were hyper-methylated and 6764 genes were hypo-methylated in the gene body region in the HC group. These differentially methylated genes were enriched in multiple pathways, including carbohydrate metabolism, insulin pathway, lipid metabolism and adipokines signaling pathway. In addition, the variations in DNA methylation significantly regulated transcription levels of key genes of metabolism which could affect the glucose concentrations and lipid deposition of grass carp. Furthermore, we compared DNA methylation alterations of genes in glucose metabolism and obesity pathways of grass carp with mammalian models in different nutritional states. The results showed that most of the DMGs in grass carp were also regulated by DNA methylation in mammals when nutritional state changed. The findings revealed more differentially methylated regions and candidate genes for glucose metabolism and broke species boundaries.